Pemanfaatan Digital Marketing dalam Membangun Brand Awareness Institusi Pendidikan Tinggi - Isti Budhi Setiawati; Jamal Ismail (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
The increasing competition among higher education institutions necessitates effective marketing strategies to build brand awareness. Digital marketing has become a crucial tool in achieving this goal. This study aims to analyze the role of digital marketing in enhancing brand awareness in higher education institutions. The research method employed is a literature review, gathering and analyzing various relevant sources, including scientific journals, books, and previous research reports. The results indicate that implementing digital marketing strategies, such as the use of social media, content marketing, and search engine optimization (SEO), significantly contributes to the enhancement of brand awareness in higher education institutions. Moreover, active interaction and relevant content on digital platforms can increase audience engagement and loyalty. The implications of this study highlight the importance for higher education institutions to integrate digital marketing into their communication strategies to expand reach and strengthen brand image in the public eye.